The Ocean 74 Conference - McKeown, D.; Grant, A. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1975)
Summary Ocean 74, the fifth IEEE International Conference on Engineering in the Ocean Environment, was held in Halifax, Nova Scotia, August 21 to 23, 1974, under the chairmanship of Ï. Ê. Gashus of Nova Scotia Technical College. This was the first time that the annual conference was held outside the USA. 529 people from many different countries attended: 125 papers by authors from 10 different countries were presented. The major portion of the work presented was oriented toward electricai and electronic engineering but the Technical Program Committee did seek papers from other disciplines to exemplify the multidisciplinary nature of oceanography. The work in temperate and Arctic waters was the main emphasis of the conference and the largest session dealt with "Engineering and Physics of Sea Ice". Other subject areas included: 1. Seismic reflection methods and geological instrumentation and techniques, 2. Positioning at sea, Acoustic applications, techniques, instrumentation, and scattering, Data acquisition, communications, telemetry, and signal processing, Instrumentation, sensing in the ocean environment, and pressure 3. tolerant electronics, 6. Pollution monitoring, fish monitoring and counting, and deep-water fishing technology, 7. Tidal power and tidal measurements in the open ocean, 8. Buoys, manned submersibles and diving technology, ship behaviour and handling, and mechanical engineering. The conference proceedings were made available prior to the conference and this appeared to stimulate discussion periods after each paper.